Reformulasi Pemimpin Usia Muda Sebagai Calon Presiden dan Wakil Presiden: Tinjauan Ius Constituendum - Razak, Askari (Fakultas Hukum Universitas Mulawarman, 2023)
This study examines the reformulation of age requirements for young leaders as candidates for President and Vice President, reflecting a shift in leadership preferences within society. The aim is to analyze the rationality of the minimum age restrictions for presidential and vice-presidential candidates and to formulate an ideal change through the ius constituendum approach, to create opportunities for the emergence of young leaders in line with contemporary political aspirations. The normative method is used with a legislative and conceptual approach through literature review and qualitative data analysis. The results show that the minimum age restriction of 35 years aims to ensure the quality of mature national leadership, although some argue that it has the potential to hinder the emergence of innovative young leaders. The ideal formulation of changes is to revise Article 6A paragraph (1) to lower the minimum age limit to 30 years, based on principles of democracy and non-discriminatory political rights based on age, involving public participation and constitutional mechanisms.